Traceability Implementation in Organic Farming: Case Study, Chamomile Tea Production - Ibrahim, Shaima Abdelfattah (AUC Knowledge Fountain, 2014)
Implementing a traceability plan in an herbal production plant is a complex task. In this study an attempt to integrate food safety, quality and traceability through the different stages of the organic German Chamomile (Matricaria recutita) production chain was made. First, all the current relevant international laws, regulations and standards regarding traceability, safety and quality, with emphasis on how and why they are necessary for any food production chain, were set forward. Second, physico-chemical and microbiological analyses were run throughout the different processing stages of production, for four different Chamomile batches produced over the same season using the same farming and processing practices throughout the production process. Third, collective data for four batches were gathered to evaluate and confirm the safety, quality, reliability and effectiveness of the processing chain and to pin point any defects, product information leaks or production risks, from occurring. Last but not least, an attempt for a cost effective, up to date traceability plan, including regular assessments, audits, evaluations and updates, was designed and recommended as a continuous protocol to be followed by the production Company thereafter. All analyses followed the latest ISO standards, WHO and the European Pharmacopeia procedural guidelines and limits respectively. Results revealed that the Chamomile organic herb conforms and complies with above standards but an upgraded traceability plan is needed to trace and/track product batches at any point in time during/after the processing chain. The recommended plan would serve as a guide for further products produced by the same Company as well as other ongoing traceability efforts in other food companies nationwide.